Cities and their Global Responsibility: Reflections on Social Ethics from a German Perspective - Becka, Michelle (Concilium, 2019)
Cities and conurbations in Europe, and especially in Germany face various social and ecological challenges. But while local social problems are usually immediately visible through phenomena such as gentrification or social segregation, ecological problems linked to the use of resources and CO2 emissions tend to be less visible here than in other parts of the world. This article calls for social and ecological issues not to be separated, and focuses on the interweaving of local and global responsibility. Cities play a particular role in the recognition of this dual responsibility, as is demonstrated by issues of climate justice, social integration and city networking.